Synthesis and biological evaluation of halo-neplanocin A as novel mechanism-based inhibitors of S-Adenosylhomocysteine hydrolase - Jeong, LS; Moon, HR; Park, JC; Shin, DH; Choi, WJ; Lee, KM; Kim, HO; Chun, MW; Kim, HD; Kim, JH (MARCEL DEKKER INC, 2003)
Halogenated analogues of neplanocin A were synthesized from the key intermediate 1, among which fluoro-neplanocin A was found to be novel mechanism-based irreversible inhibitor of S-Adenosylhomocysteine hydrolase.